Sound Governance: Model Kolaborasi Multilevel sebagai Upaya Pencegahan Korupsi dalam Pemerintahan Desa: - - Nike Mutiara Fauziah; Ria Karlina Lubis (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2022)
There is a direct impact between governance and corruption. They also evolve over time. For governance, the development of the concept has brought us to Sound Governance, a concept that is suitable and responds to international norms of governance. While the development concept has concluded the Sustainable Development Goals (SDGs), one of the Goals is the establishment of a strong institution. This work was conducted in the law and policy framework using regulations and public policy as the main reference for analyzing and evaluating purposes. The result has shown that implementation of Sound Governance with the adoption of Goal 16 target and indicator is the useful mean for corruption prevention and the for village governance.